Helping Infant Economies Grow: Foundations of Trade Policies for Developing Countries - Greenwald, Bruce; Stiglitz, Joseph E (American Economic Review, 2006)
Helping Infant Economies Grow: Foundations of Trade Policies for Developing Countries by Bruce Greenwald and Joseph E. Stiglitz. Published in volume 96, issue 2, pages 141-146 of American Economic Review, May 2006